Educare all’opera: un’esperienza di museo inclusivo presso il Teatro di San Carlo - Dinko Fabris (Musica Docta)
The Teatro San Carlo Museum was inaugurated in 2011 with the aim of preserving the historical and artistic heritage of the oldest opera house still in operation. For this reason it has been named “MeMus”, combining the words “memory” and “music”. However, the three-century-old history of the San Carlo in Naples will be explored through a contemporary and modern approach, using innovative and attractive technologies, in addition to the historical materials on permanent display or in temporary exhibitions, and designed especially for the youngest visitors. Since 2020 and until December 2023, I have been in charge of a new Department of Research, Publishing and Communication at San Carlo, which includes the Historical Archives and the Museum. We have thus been able to experiment with the role of musicology in such a specific reality. During the Covid-19 pandemic, I immediately thought that the museum should be a laboratory where we could study how to transmit a long and complex musical history to the younger generations in a way that was accessible and inclusive for all disabilities: we created panels with transcriptions in Braille, audio guides, accessible itineraries and tactile workshops. The case of the illustrated book Ritorno all’opera, published by Edizioni San Carlo in 2022 and transformed into an interactive multimedia installation in the museum, is described in the paper as an example of an accessible and inclusive activity for all types of users.